(untitled) (Proceedings of International Conference on Educational Discoveries and Humanities, 2024)
In today’s world, liver cirrhosis has become a prevalent and serious healthcare issue affecting millions of people worldwide. This chronic liver condition is often triggered by various factors such as excessive alcohol consumption, viral hepatitis, and obesity. However, it is important to understand the role that the surrounding environment and working conditions play in the development of liver cirrhosis. This article examines whether the environment and work conditions are a contributing factor to the development of liver cirrhosis"